Effect of service quality on Go-Food customer satisfaction in Bandung - Putri Trulline; Asep Suryana; Dadang Sugiana; Uud Wahyudin (Faculty of Communications Science, Dr. Soetomo University, 2025)
The rapid advancement of digital technology has made online food delivery services an integral aspect of modern lifestyles, enhancing convenience through technology-based marketing initiatives. GoFood, a feature within the GoJek application, is an online food ordering service with significant influence on user activity and experience. This study aims to examine the effect of service quality on customer satisfaction, specifically for GoFood users in the city of Bandung. The quantitative research design employed incidental sampling to select 110 respondents who met the predetermined criteria. The questionnaire used was intended for students, lecturers, activists, or other occupations who are active as GoFood customers on the GO-JEK application. Data were analysed to evaluate the relationship between service quality variables, including reliability, empathy, and responsiveness, with customer satisfaction using multiple regression analysis techniques. The analysis results show that service quality variables such as reliability and empathy significantly affect consumer satisfaction, and one variable, responsiveness, negatively impacts customer satisfaction. With an adjusted R-square value of 55.1%, the independent variable in the model accounts for 55.1% of the dependent variable, with other factors outside the model accounting for the remaining portion. The finding suggests that overemphasising speed or responsiveness may not necessarily improve GoFood customer satisfaction and, in the context of this study, may even have a negative effect. These results can be interpreted as indicating that consumers may prioritise other service qualities, such as order accuracy or reliability, over response speed.